Outcome of Modified Salter Osteotomy in Improving Acetabulum Index of Developmental Dysplasia of the Hip with Age Group of 2-10 Years: Outcome of Modified Salter Osteotomy on Acetabular Index in Children Aged 2–10 Years - Ahmed, Mehtab; Ali, Pervez; Soomro, Shazia; Jamali, Abdul Ghaffar; Ali, Faique; Ahmed, Hassan (Pakistan Journal of Health Sciences, 2026)
The modified Salter osteotomy is a widely utilized surgical intervention for treating developmental dysplasia of the hip (DDH). Objectives: To assess the outcome of modified Salter osteotomy in improving the acetabular index (AI) in children with DDH aged 2-10 years. Methods: This observational cohort study was conducted at the Department of Orthopedics, JPMC, Karachi, from December 2024 to September 2025. Sixty children aged 2–10 years with DDH undergoing modified Salter osteotomy were included. Baseline demographics, clinical examination, and preoperative radiographs for AI were recorded. Outcomes included change in AI, radiological grading by Severin classification, and clinical results by Modified MacKay criteria at 3 and 6 months. Data were analyzed using SPSS version 26.0 with non-parametric tests, Chi-square/Fisher’s exact test, and Kappa statistic, taking p<0.05 as significant. Results: In a total of 60 children, 12 (20.0%) were boys, and 48 (80.0%) were girls, with a median age of 7 (5.5–9) years, and BMI 25 (23.0–27.0) kg/m². The median AI decreased significantly from 39.00 (35.00–43.00) preoperatively to 21.00 (18.00–25.00) at 6 months (p<0.001). At 6 months, radiological outcomes were excellent in 24 (40.0%), good in 20 (33.3%), fair in 10 (16.7%), and poor in 6 (10.0%). Clinical outcomes were excellent in 22 (36.7%), good in 21 (35.0%), fair in 11 (18.3%), and poor in 6 (10.0%). Agreement between the two systems was substantial (κ=0.71, p<0.001). Conclusions: Modified Salter osteotomy resulted in a significant improvement in AI among children with DDH, accompanied by favorable radiological and clinical outcomes at six months.